Effect of added copper and full fat soybean meal on growth performance and carcass properties in broiler chickens - Salajpal, Krešimir; Grbeša, Drako; Kapš, Miroslav; Kiš, Goran; Karolyi, Danijel (Acta Agraria Kaposváriensis, 2006)
A 2 × 3 factorial experiment was conducted using a total of 504, 1 day old, Cob 500® commercial broilers to determine the effect of added copper (0 or 250 ppm) and full fat soybean meal level (10, 20 and 30%) on the growth performance and carcass properties in broiler chickens. The chickens fed 250 ppm copper as copper sulfate had lower (P < 0.05) average daily gain and lower finally average body weight then chickens fed no added copper diets. Also, added copper impaired (P < 0.05) feed conversion ratio during 49-d experimental period. The chickens fed with 30% full fat soybean meal in diet had higher (P < 0.01) average daily gain during day 7 to 49 and higher (P < 0.01) average body weight at day 49 then those consuming other diets. The addition of 250 ppm of copper improved dressing percentage (P < 0.01), increased (P < 0.05) lightness of breast muscle and tended to reduce abdominal fat content (P < 0.06). The results indicate that the addition of 250 ppm copper to broiler diets have adverse effect on growth performance, but improve dressing percentage and decrease abdominal fat content. Using a 30% of full fat soybean meal in a broiler diet improves growth performance without negative effect on dressing percentage and abdominal fat content in 49 days fattening period.